Relationship between Family System Support and Diet Compliance in Diabetes Mellitus Patients - Hendra, Donny; Putra, Ifon Driposwana; Marcelina, Sri; Simamora, Asnil Adli (Universitas Prima Indonesia, 2025)
The diabetes diet is carried out to regulate eating patterns according to the portions determined for DM sufferers. by maintaining the 3Js, namely the number, type, and schedule of the DM diet. The research aims to determine the relationship between Family System Support and Diet Compliance in Diabetes Mellitus Patients. This type of research has a quantitative and descriptive design. The research population was 228 diabetes mellitus patients, and the sample was 39 people, using an accidental sampling technique. The research instrument is a questionnaire, and computerized data processing using SPSS, with univariate and bivariate data analysis. The research results showed that the majority of respondents in the Family Support System group were 39 people lacking (56.5%) and respondents in the non-compliant group were 44 people (63.8%). The results of the chi-square test showed that there was a relationship between family support system and dietary compliance in diabetes mellitus patients with p.value = 0.015 < 0.05. It is hoped that the health center will provide education and information to DM patients by making leaflets and posters about DM, especially DM treatment to control blood glucose levels and prevent complications and always socialize something new to treat DM by continuing to update knowledge about DM in particular.